The Analysis of Teachers’ Difficulties in Teaching Mathematics at SMAN 2 Tambang - Ivan Septian Rahmad; Darmansyah (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
Teachers must have teaching skills and create a comfortable, joyful, relax, and serious learning atmosphere. Therefore, teachers must understand the learning process, must be aware of the learners’ psychologies, and capable of developing the learners’ interest so they have greater spirits to learn. From various problems of teaching mathematics, the teacher's position is the center of the problem. Teachers as motivators, educators, and supervisors have important roles to direct learners to be capable and to actualize them in real life through the school lessons. There are several factors of difficulties experienced by mathematics teachers in implementing learning at SMAN 2 Tambang. This research aims to determine the difficulties experienced by mathematics teachers in implementing learning. This type of writing uses a descriptive qualitative approach. The subjects of this research were teachers at SMAN 2 Tambang. Data collection techniques used interviews and questionnaires. It could be concluded that the most common difficulty was determining the learning media and learning process planning. The cause was the limitation of facilities, infrastructures, and unfordable media by the learners. On the other hand, the next difficulties were due to the large number of learners that could not be accommodated in a small classroom.